HISTORICAL ASPECT OF EXEMPTION FROM CRIMINAL PUNISHMENT DURING THE RISING OF THE SOVIET STATE - V. A. Terentieva (Вестник Кемеровского государственного университета, 2014)
The paper investigates the historical aspect of exemption from punishment in the Soviet period. The aim of the research is to study the history of the origin and enhancement of such grounds for exemption from criminal punishment as parole, lapse of time, and others.